﻿﻿Separation of Three Flavones inChamaecyparis obtusa by Using Solid-Phase Extraction - Tian, M.; Row, H.S.; Row, K.H. (Asian Journal of Chemistry, 2010)
Three primary flavones components, amentoflavone, quercitrin and myricetin were extracted from Chamaecyparis obtusa leaves by refluxing in methanol and separated by gradient elution by RP-HPLC. Solid-phase extraction with different polarity solvents was applied to separate the components from the extract of methanol. 3.040 mg/g for myricetin, 0.0908 mg/g for quercitrin and 0.514 mg/g for amentoflavone can be obtained.